2004
DOI: 10.1158/0008-5472.can-04-0364
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Colorectal Cancer Liver Metastasis and Extension of Survival by Expression of Apolipoprotein(a) Kringles

Abstract: The formation of hepatic metastases in colorectal cancer is the main cause of patient death. Current therapies directed at hepatic metastasis of colorectal cancer have had minimal impact on outcome. Therefore, alternative treatment strategies for liver metastasis require development. The present study was performed to evaluate the application of cDNA of LK68 encoding apolipoprotein(a) kringles IV-9, IV-10, and V as possible candidates for gene therapy treatment of this life-threatening disease. The murine colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…At the protein level, Kim et al 10 and Yu et al 11,12 demonstrated that the vascularity in LK68-treated tumor tissues was greatly reduced, and the expression of angiogenin, VEGF, and basic fibroblast growth factor (bFGF), which switch on the angiogenic phenotype in tumor tissues, was dramatically decreased at peripheral regions of the tumors. Similarly, LK8 was found to inhibit the migration of HUVECs in a dose-dependent manner in vitro and new capillary formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the protein level, Kim et al 10 and Yu et al 11,12 demonstrated that the vascularity in LK68-treated tumor tissues was greatly reduced, and the expression of angiogenin, VEGF, and basic fibroblast growth factor (bFGF), which switch on the angiogenic phenotype in tumor tissues, was dramatically decreased at peripheral regions of the tumors. Similarly, LK8 was found to inhibit the migration of HUVECs in a dose-dependent manner in vitro and new capillary formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferation inhibition and wound migration assays were performed as previously described in detail elswhere. 11,24 Animals. Five-week-old male BALB/c nu/nu mice (Charles River, Yokohama, Japan) were housed in a sterile environment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Briefly, 125-day-old female SCID mice were anesthetized with a ketamine (Ketaminol 75 mg kg À1 ; Intervet, Boxmeer, the Netherlands)/dexmedetomidine (Dexdormitor 1 mg kg À1 ; Orion Pharm., Espoo, Finland) admixture and the spleen was exteriorized through a left lateral flank incision. Tumors were established by intrasplenic injection of 1 Â 10e6 HT29 cells as described earlier.…”
Section: Animalsmentioning
confidence: 99%